Constructing Uniform Approximate Analytical Solutions for the Blasius Problem - Beong In Yun (Abstract and Applied Analysis)
We propose a simple constructive method which assures uniform accuracy of the approximate analytical solutions for the Blasius problem on the semi-infinite interval 0,∞. The method is based on a weight function having an S-shape to reflect a series solution near the origin x=0 and a reference solution far from the origin. Numerical results show the efficiency of the proposed method.